Permanent-income inequality - Brant Abbott; Giovanni Gallipoli (Quantitative Economics, 2022)
Through certainty equivalent consumption (CE) measures, we show that dispersion of current earnings, expenditures, and net worth overstate welfare inequality. This is largely due to the unaccounted value of future earnings, which we call human wealth. The latter mitigates permanent-income inequality, though its influence is diminished by the growing importance of assets in lifetime wealth. Average expenditures and CE inequality roughly doubled between 1983 and 2016 and, to weigh these offsetting forces, we decompose aggregate welfare changes into contributions from the level and dispersion of consumption, as well as uncertainty and demographic composition. Rising inequality has offset about 1/4 of the welfare gains from higher consumption, with most of the losses accruing after 2000.
Keywords: D31; E2; E21; I24; 330; Wealth; human capital; permanent income; consumption; inequality